Efficacy of High Flow Nasal Cannula Versus Noninvasive Ventilation in Acute Exacerbation of COPD - Tehzeeb Ashraf; Muhammad Rauf Ul Hassan; Muhammad Asif; Niaz Liaqat (Indus Journal of Bioscience Research, 2025)
Introduction: COPD is a familiar treatable disorder, Despite the availability of various treatment options, there is limited local evidence to guide the most effective and accessible treatment strategies in resource-constrained settings, Non-Invasive Ventilation (NIV) has been widely used as the standard of care for managing AECOPD; however, recent advancements, such as High-Flow Nasal Cannula (HFNC), offer a promising alternative. Materials & Methods: There were 200 patients with acute exacerbations of COPD, both male and female, ranging in age from 20 to 70. Individuals suffering from systemic illnesses such as chronic liver disease, heart failure, renal failure, hematological disorders, bronchiectasis, pneumonia, life-threatening hypoxemia, agitation, confusion, bowel obstruction, vomiting, upper gastrointestinal surgery, hemodynamic instability requiring pressors or inotropes, trauma, facial burns, or recent upper airway or facial surgery were not included. Group A received non-invasive ventilation (NIV). Group B received high flow nasal oxygen treatment. The following parameters were used to determine the frequency of treatment success: pH >7.35, a decrease in PaCO2 of >15–20% with SaO2 (with or without oxygen) of >90%, and a decrease in respiratory rate of >20% compared with spontaneous breathing. All patients were monitored for 24 hours. Results: The study’s age range was 20 to 70 years old, with a mean age of 57.79 ± 4.93 years. Patients in group A were 57.69 ± 5.01 years old on average, while those in the group B were 57.84 ± 4.91 years old. Out of 200 patients, 132 (66.0%) were males and 68 (34.0%) were females with male to female ratio of 1.9:1. At the end of 24 hours of treatment, 73 patients (73.0%) in group A (noninvasive ventilation) and 89 patients (89.0%) in group B (nasal high-flow oxygen) showed successful with 0.0039 significant p-value. Conclusion: This study demonstrated the efficacy of nasal high-flow oxygen is better than noninvasive ventilation in acute exacerbation of COPD.